Peran Guru Sebagai Motivator Dalam Minat Belajar Siswa Kelas I di SDIP YLPI Pekanbaru - Rohani, Fika; Siti Quratul Ain (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2023)
This study aims to describe the teacher's role as a motivator in the learning interest of grade I students at SDIP YLPI Pekanbaru. This study uses qualitative research with descriptive methods. This study used three data collection techniques, namely interviews, observation, and documentation. The data analysis technique used is according to Miles and Huberman. The results showed that the teacher had carried out the teacher's role as a motivator in the learning interest of grade I students by giving grades or numbers, giving prizes, creating competition, giving praise, giving punishment, giving tests and evaluations, using various learning methods, and informing student learning outcomes